SAFETY OF DIURETIC ADMINISTRATION IN EARLY DYSPNEA PATIENTS NOT FINALLY DIAGNOSED WITH ACUTE HEART FAILURE: A CLINICAL STUDY. - Saubhagya Chhotaray; Bhupesh Kumar Nayak; Gopabandhu Patra; Chhatray Marndi (Student's Journal of Health Research, 2023)
Objectives The study aims to investigate the effect of initiating diuretic treatment in dyspnea patients without a confirmed diagnosis of acute heart failure, assessing its connection with immediate medical outcomes, mortality, and readmission rates. Additionally, the study explores potential variations in treatment effects across subgroups and provides insights into the implications of diuretic administration in the emergency department.  Methods This study, conducted at Bhima Bhoi Medical College in Balangir, Odisha, India, employed exploratory secondary analysis of BASEL-V registry data, examining 266 dyspnoeic patients diagnosed with conditions other than AHF. The analysis assessed outcomes, categorizing patients into treated and untreated groups, with statistical methods including Wilcoxon rank-sum, chi-square tests, and t-test. Results Of 533 initial patients from the BASEL-V registry, 266 were analysed, with 14.6% receiving diuretics during their ED stay. The 30-day mortality rate was 4.5%, with a 5.2% mortality rate in treated patients and 4.3% in untreated patients, resulting in a non-significant adjusted hazard ratio of 1.33 for treated patients. For the secondary outcome, 13.9% experienced readmission within 30 days, with a 14.7% rate for treated patients and 10.8% for untreated patients. Conclusion The study revealed that diuretic administration in dyspnoeic patients without acute heart failure had not significantly impacted the readmission or mortality rates. While an increased hazard ratio for thirty-day mortality was observed in treated patients, it was not statistically significant, suggesting a need for cautious interpretation and further research validation. Recommendation The study recommends further research to validate and refine findings, emphasizing a larger sample size. Additionally, exploration of specific subgroups, such as those with COPD, and a comprehensive investigation into the impact of diuretic administration on elderly patients are advised for a more nuanced understanding of therapeutic implications.